Examining the Determinants of E-Wallet Continuance: An Application of Extended Technology Continuance Theory in Financial Technology - Ni Luh Putu Widia Ananda Sari; Ni Putu Sri Harta Mimba (Universitas Pendidikan Ganesha, 2024)
This study explores factors affecting the continuance intention of e-wallet usage in Bali, applying the extended Technology Continuance Theory (TCT) with added variables of perceived savings and perceived trust. Due to limited research on the impact of perceived savings and trust on e-wallet continuance intention, it is necessary to explore their integration into the Technology Continuance Theory (TCT) to enhance understanding in this area. Targeting active e-wallet users aged 17 and above, the research surveyed 160 respondents through an online questionnaire. Data analysis was conducted using SEM-PLS and Smart PLS software. The results reveal that confirmation significantly enhances perceived usefulness and satisfaction, both of which, along with perceived ease of use, significantly impact continuance intention.